Muscle paths in biomechanical multibody simulations - Maas, Ramona; Leyendecker, Sigrid (Proceedings of the ECCOMAS Thematic Conference on Mutlibody Dynamics, 2013)
When simulating biomechanical motion with multibody systems representing bones and joints, the actuation of those systems can be implemented via Hill-type muscle models. The essential task of these models is to represent the typical force-length and force-velocity relation of real muscles, hence the muscle length, the contraction velocity and the force direction of every muscle has to be provided in every time step of a dynamical simulation. This work concerns the question, how to approximate the muscle path during a dynamical simulation such that its dynamically changing behaviour is represented, while the computational effort is kept in a reasonable range, allowing the application within optimal control simulations of biomechanical motion. We show the implementation of such an algorithm in an optimal control simulation framework for biomechanical systems like the human arm by augmenting a discrete mechanics and optimal control formulation called DMOCC, which benefits from the usage of a variational integrator and therefore guarantees structure preserving simulation result
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.ltd.muscle
Keywords: Biomechanics; DMOCC; Dynamical muscle path; Hill-type muscle model; Optimal control; Structure preserving integration